The Influence of Management Control Systems and Work Motivation on Employee Performance - Sani Pertiwi; Ayke Nuraliati; Dedy Sudarmadi (Business Management, 2026)
This study aims to determine the effect of management control systems and work motivation on employee performance at the National Land Agency (BPN) of Bandung City. Employee performance in public sector organizations is an important factor in improving the quality of public services, particularly in land administration services. Problems such as delays in service completion, bureaucratic complexity, and limited adaptability to digital-based services indicate that employee performance still needs improvement. Therefore, organizations are required to implement effective management control systems and increase employee work motivation in order to support optimal organizational performance.This research uses a quantitative approach with explanatory research methods. The variables examined in this study consist of management control systems as the first independent variable, work motivation as the second independent variable, and employee performance as the dependent variable. Data were collected through questionnaires distributed to employees of the National Land Agency of Bandung City. The data analysis technique used is Structural Equation Modeling–Partial Least Squares (SEM-PLS).The results of the study indicate that management control systems have a positive and significant effect on employee performance. Effective implementation of management control systems is able to improve work discipline, coordination, supervision, and employee responsibility in carrying out organizational tasks. In addition, work motivation also has a positive and significant effect on employee performance. Employees who have high work motivation tend to work more productively, responsibly, and optimally in providing public services.The findings of this study indicate that improving employee performance in public sector organizations can be achieved through the implementation of effective management control systems and increased employee work motivation. This research is expected to contribute to the development of management accounting and human resource management literature, particularly regarding employee performance improvement in public sector organizations.